Zircon U-Pb dating, geochemistry, and Sr-Nd-Hf isotopes of the Puchang mafic dikes: implications for magmatic evolution of the Tarim large igneous province - Hu, Dongqiang; Li, Yanjun; Zhang, Qiang; Li, Hui (Frontiers in Earth Science, 2026)
The Tarim Large Igneous Province (TLIP), as a major igneous province in China, has long been a focus of geological research due to its complex rock assemblages and genetic mechanisms. This study investigates the Permian mafic dikes (diabase and sillite) in the Puchang area of the TLIP, combining zircon U-Pb geochronology, major-trace element geochemistry, and Sr-Nd-Hf isotopic analyses to reveal their petrogenesis and tectonic evolutionary significance. Zircon dating results show that the weighted mean ages of diabase and sillite are 273 ± 3 Ma and 272 ± 2 Ma, respectively, indicating their formation in the late Early Permian. Geochemically, the diabase exhibits medium-K calc-alkaline affinities, with enriched light rare earth elements ((La/Yb)n = 4.62–13.81) and negative anomalies in Nb, Ta, and Ti, while the sillite belongs to the low-K calc-alkaline series, showing weak REE fractionation. Both of the diabase and sillite are similar to OIB patterns in trace element compositions. Both rock types have εHf(t) values of −2.5 to +1.2, (87Sr/86Sr)ᵢ of 0.70431–0.70522, and εNd(t) of 0.20–0.57, reflecting depleted mantle characteristics. Lithological and geochemical evidence indicate that the magmatic source was garnet-spinel lherzolite derived from low-degree partial melting of continental lithospheric mantle metasomatized by subduction components. The magmas underwent fractional crystallization of Fe-Ti oxides and pyroxene with minor crustal contamination during evolution. Combined with regional tectonic evolution, these Puchang mafic dikes formed in the late stage (273–272 Ma) of lithospheric thinning caused by mantle plume thermal erosion, serving as an important supplement to the “mantle plume-lithosphere interaction” model of the TLIP. This study provides new insights into the source properties and tectonic setting of the multiphase magmatism in the TLIP.